A Cecropin-4 Derived Peptide C18 Inhibits Candida albicans by Disturbing Mitochondrial Function - Sun, Chao-Qin; Peng, Jian; Yang, Long-Bing; Jiao, Zheng-Long; Zhou, Luo-Xiong; Tao, Ru-Yu; Zhu, Li-Juan; Tian, Zhu-Qing; Huang, Ming-Jiao; Guo, Guo (Frontiers in Microbiology, 2022)
Global burden of fungal infections and related health risk has accelerated at an incredible pace and multidrug resistance emergency aggravates the need for the development of new effective strategies. Candida albicans (C.albicans) is clinically the most ubiquitous pathogenic fungus that lead to high incidence and mortality in immunocompromised patients. Antimicrobial peptides (AMPs) in this context represent promising alternatives having potential to be exploited for improving human health. In our previous studies, a Cecropin-4 derived peptide named C18 was found to possesses a broader antibacterial spectrum after modification and exhibits significant antifungal activity against C.albicans. In this study, C18 shows antifungal activity against C.albicans or non-albicans Candida species with a minimum inhibitory concentration (MIC) at 4~32μg/mL, and clinical isolates of fluconazole (FLZ)-resistance C. tropicalis were highly susceptible to C18 with MIC=4~32μg/mL. Additionally, C18 is superior to FLZ for killing planktonic C.albicans from inhibitory and killing kinetics curves. Moreover, C18 could attenuate the virulence of C.albicans including damaging the cell structure, retarding hyphae transition and inhibiting biofilm formation. Intriguingly, in the Galleria.mellonella (G. mellonella) model with C.albicans infection, C18 could improve the survival rate of G. mellonella larvae to 70% and reduce C.albicans load from 5.01×107 CFU to 5.62×104 CFU. For mechanistic action of C18, the level of reactive oxygen species (ROS) generation and cytosolic Ca2+ increased in the presence of C18, which is closely associated with mitochondrial dysfunction. Meanwhile, mitochondrial membrane potential (△m) loss and ATP depletion of C.albicans occurred with the treatment of C18. We hypothesized that C18 might inhibit C.albicans via triggering mitochondrial dysfunction driven by ROS generation and Ca2+ accumulation. Our observation provides a basis for future research to explore the antifungal strategies and presents C18 as an attractive therapeutic candidate to be developed to treat candidiasis.